The incidence, characteristics and outcomes of pregnant women hospitalized with symptomatic and asymptomatic SARS-CoV-2 infection in the UK from March to September 2020: A national cohort study using the UK Obstetric Surveillance System (UKOSS). - Nicola Vousden; Kathryn Bunch; Edward Morris; Nigel Simpson; Christopher Gale; Patrick O'Brien; Maria Quigley; Peter Brocklehurst; Jennifer J Kurinczuk; Marian Knight (PLoS ONE)
Background There is a lack of population level data on risk factors, incidence and impact of SARS-CoV-2 infection in pregnant women and their babies. The primary aim of this study was to describe the incidence, characteristics and outcomes of hospitalized pregnant women with symptomatic and asymptomatic SARS-CoV-2 in the UK compared to pregnant women without SARS-CoV-2. Methods and findings We conducted a national, prospective cohort study of all hospitalized pregnant women with confirmed SARS-CoV-2 from 01/03/2020 to 31/08/2020 using the UK Obstetric Surveillance System. Incidence rates were estimated using national maternity data. Overall, 1148 hospitalized women had confirmed SARS-CoV-2 in pregnancy, 63% of which were symptomatic. The estimated incidence of hospitalization with symptomatic SARS-CoV-2 was 2.0 per 1000 maternities (95% CI 1.9-2.2) and for asymptomatic SARS-CoV-2 was 1.2 per 1000 maternities (95% CI 1.1-1.4). Compared to pregnant women without SARS-CoV-2, women hospitalized with symptomatic SARS-CoV-2 were more likely to be overweight or obese (adjusted OR 1.86, (95% CI 1.39-2.48) and aOR 2.07 (1.53-2.29)), to be of Black, Asian or Other minority ethnic group (aOR 6.24, (3.93-9.90), aOR 4.36, (3.19-5.95) and aOR 12.95, (4.93-34.01)), and to have a relevant medical comorbidity (aOR 1.83 (1.32-2.54)). Hospitalized pregnant women with symptomatic SARS-CoV-2 were more likely to be admitted to intensive care (aOR 57.67, (7.80-426.70)) but the absolute risk of poor outcomes was low. Cesarean births and neonatal unit admission were increased regardless of symptom status (symptomatic aOR 2.60, (1.97-3.42) and aOR 3.08, (1.99-4.77); asymptomatic aOR 2.02, (1.52-2.70) and aOR 1.84, (1.12-3.03)). The risks of stillbirth or neonatal death were not significantly increased, regardless of symptom status. Conclusions We have identified factors that increase the risk of symptomatic and asymptomatic SARS-CoV-2 in pregnancy. Clinicians can be reassured that the majority of women do not experience severe complications of SARS-CoV-2 in pregnancy.